Seepage Analysis and Optimization of Reservoir Earthen Embankment with Double Textured HDPE Geo-Membrane Barrier - Kennedy C. Onyelowe; Akash Nimbalkar; Narala G. Reddy; Jair de Jesus A. Baldovino; Shadi Hanandeh; Ahmed M. Ebid (Civil Engineering Journal, 2023)
This research paper focuses on conducting a steady state seepage analysis along with the downstream slope factor of safety using the Modified Bishops method in a poorly compacted earthen embankment and optimizing the same reservoir earthen embankment in a case study located near Sadiyavav village in Junagadh district in Gujarat, India. The study site, situated at 21°32'06.5"N and 70°37'26.7"E, is renowned for its Asiatic lions. The analysis and optimization were performed with a double-textured High-Density Polyethylene (HDPE) Geo-membrane barrier. Previously, designs and numerical solutions proposed homogenous embankments and too poorly compacted with no drainage arrangements, which led to anisotropic conditions within the section and water seeping out, cutting the phreatic line. The paper presents the documented improvements in the factor of safety achieved through the seepage analysis and the optimization of the HDPE Geo-membrane barrier. Two improvement techniques were studied using the “Limiting Equilibrium-Finite Element Method” (LS-FEM). The first using (HDPE) Geo-membrane stabilized with gabions, and the second alternative using HDPE Geo-membrane with gabions in addition to rock toe. The study results showed improvements in the downstream slope stability for the two alternatives by 3% and 10%, respectively. Doi: 10.28991/CEJ-2023-09-11-07 Full Text: PDF